Oncology patients' perception of physicians who use an integrated electronic health record (EHR) during clinic visits: PRIME‐EHR double‐blind, randomized controlled trial. Issue 21 (15th July 2021) - Haider, Ali; Azhar, Ahsan; Tanco, Kimberson C.; Epner, Margeaux; Naqvi, Syed Mussadiq Ali Akber; Abdelghani, Eman; Reddy, Akhila; Dev, Rony; Wu, Jimin; Bruera, Eduardo
Abstract : Background: Patients with cancer prefer and positively perceive physicians who communicate face‐to‐face without the use of a computer. However, the use of electronic health records (EHRs) in the examination room remains a practical necessity. On the basis of existing literature, the authors developed and tested an integration model, PRIME‐EHR, that focuses on the best‐practice guidelines. To their knowledge, no randomized controlled trials (RCTs) have been conducted to test the effectiveness of such models. Methods: In this double‐blind, crossover RCT, 120 eligible patients with cancer were enrolled between April 1, 2019 and February 15, 2020 at The University of Texas MD Anderson Cancer Center. The objectives were to compare patients' perceptions of physicians' skills and their overall preference after they watched 2 standardized, scripted video vignettes of physicians: 1 portraying the use of a standard EHR and the other portraying the use of a PRIME‐EHR. Actors and patients were blinded to the purpose of the study. Investigators were blinded to the sequence of videos watched by the patients. Validated questionnaires to rate physicians' compassion (0 = best, 50 = worst), communication skills (14 = poor, 70 = excellent), and professionalism (4 = poor, 20 = very good) were used. Results: PRIME‐EHR, compared with the standard EHR, resulted in better scores for physician compassion (median score, 5 [interquartile range, 0‐10] vs 12 [interquartile range, 4‐25]; P = .0009), communication skills (median score, 69 [interquartile range, 63‐70] vs 61 [interquartile range, 50‐69]; P = .0026), and professionalism (median score, 20 [interquartile range, 18‐20] vs 18 [interquartile range, 14‐20]; P = .0058). The majority of patients preferred physicians who used PRIME‐EHR (n = 70 [77%] vs n = 21 [23%]; P < .0001). Conclusions: The PRIME‐EHR approach significantly improved patients' perceptions of and preference for the physicians. This integrated model of health care delivery has the potential to improve communication and compassion in cancer care. Abstract : In this double‐blinded, randomized controlled trial that includes 120 patients with cancer, the "PRIME‐Electronic Health Record" integration model results in significantly better scores for physicians' compassion, professionalism, and communication skills. This integrated model of health care delivery has the potential to improve communication and compassion in cancer care.